El desarrollo tecnológico en la vida cotidiana: influencias sociales comprendidas por universitarios brasileños - Veraszto, Estéfano Vizconde; Silva, Dirceu da; García, Francisco García; Barros Filho, Jomar; Miranda, Nonato Assis de; Amaral, Ségio Ferreira; Camargo, Éder Pires de [UNESP] (My University, 2010)
This paper, trying to understand how society influences technological development in daily life, developed a theoretical model, translated into a Likert scale, to be applicable to Brazilians undergraduate students from Sao Paulo. The social indicators that are presented in this scale were generated from content analysis in the process of construction and presentation of qualitative results which are the goals of this article. So it is possible to point out that the sample of undergraduates students surveyed points to the government, educational and research institutions, companies and citizens, as the main social actors strictly responsible for technology choices. The result allows brief reflections on the social influence on technology choices in daily life.

Para entender cómo la sociedad influye en el desarrollo tecnológico en la vida cotidiana, este trabajo desarrolló un modelo teórico traducido en escala de Likert para aplicación con estudiantes universitarios brasileños del Estado de São Paulo. Los indicadores sociales presentes en la escala fueron generados a partir de Análisis de Contenido. La presentación cualitativa de los resultados del análisis de los indicadores, que es el objetivo central de este artículo, permite apuntar que los estudiantes encuestados tienen el gobierno, las instituciones educativas y investigativas, las empresas y los ciudadanos, como los principales actores sociales responsables por el desarrollo tecnológico. Con esto, se puede también presentar conclusiones que reflejan sobre la influencia social en las elecciones tecnológicas en el cotidiano.
Keywords: Technology; Society; Everyday life; Public perception; Tecnología; Sociedad; Vida cotidiana; Percepción pública